First trimester serum biomarkers to predict gestational diabetes in a high-risk cohort: Striving for clinically useful thresholds. (March 2018) - Corcoran, Siobhan M.; Achamallah, Natalie; Loughlin, John O'; Stafford, Philip; Dicker, Pat; Malone, Fergal D.; Breathnach, Fionnuala
Abstract: Objectives: Screening and diagnosis of gestational diabetes (GDM) has been a source of controversy. The prevalence has increased in line with an obesity epidemic and a trend towards delayed child-bearing. Treatment of even modest glycaemic impairment in pregnancy has been shown to be beneficial in preventing its clinical sequalae. However the cumbersome nature and timing of the oral glucose tolerance test coupled with debate around universal versus risk factor based screening have been problematic. This group aimed to investigate a panel of biomarkers which have shown promise in the literature to predict GDM from the first trimester in a group of high risk women. Methods: Serum samples were drawn on 248 women deemed at risk of GDM before 15 weeks' gestation to measure C-reactive protein, sex hormone binding globulin, adiponectin and 1, 5 anhydroglucitol. Patients underwent an oral glucose tolerance test as per IADPSG criteria at 28 weeks' gestation. Multiple logistic regression was used to examine the link between incidence of GDM and early pregnancy serum biomarkers. Results: Adiponectin levels in the first trimester are independently linked to the risk of GDM. Serum adiponectin <8.9 μg/ml gives an odds ratio of 3.3 for GDM.Mean 1, 5 AG levels are significantly lower in those that go on to develop GDM. SHBG levels measured in the first trimester were linked to the risk of GDM. However, this was no longer statistically significant once BMI, ethnicity and family history were taken into consideration. First trimester measurement of CRP is not a useful indicator of GDM risk. Conclusions: First trimester measurement of Adiponectin and 1, 5 Anhydroglucitol are potential early biomarkers for the later onset of GDM. Risk stratification using these biomarkers may facilitate early diagnosis and management of GDM to mitigate against its complications.